Loverly the life and times of "My fair lady" - McHugh, Dominic (Broadway legacies, 2012)
This text considers one of the most popular musicals of all time, Lerner and Loewe's 'My Fair Lady.' Using previously-unpublished letters and documents, author Dominic McHugh presents a behind-the-scenes look at the creation of the show, revealing the tensions that went into the making of this beloved musical